Keterkaitan Profil Risiko dengan Preferensi Investasi: Mengungkap Cara Pandang Investor melalui Simulasi Investasi Saham di Bursa Efek Indonesia - Purwaningrum, Endang; ali; Ingriyani, Lini; Fatimah, Fatimah; Aminah, Indianik; Waersini, Sabar; Masjono Muchtar, Ali (ISAS (Indonesian Society of Applied Science), 2025)
It is common knowledge in the investment world that investor candidates will look at their risk profile before determining what investment is suitable. This article aims to see the relationship between risk profile and the type of investment chosen. At the initial stage respondents were asked to answer questions to determine their risk profile. In the second stage, 40 respondents were given a deeper understanding of investment, in the third stage respondents would conduct a stock investment simulation, then respondents would trade stocks themselves according to the direction and guidance of the mentor. Three months later, respondents were surveyed about stock investment and their understanding of investments. Respondents were dominated by women and aged between 30-40 years, had jobs or were housewives. There is a relationship between risk profile and the type of investment preferred. Aggressive profiles tend to choose investments in stocks and bonds, Moderate profiles tend to choose gold and stock investments. Conservative profiles tend to choose gold and property investments. The implication is that the risk profile is used as a reference in determining the type of investment. There is a change in the way participants view investing due to risk profile factors and factors of increasing knowledge about investment, but gold investment is still the main choice because the risk profile of participants is dominated by conservative and moderate profiles.